342 Asking the right questions—understanding child farm-related injury and death. (20th November 2022) - Adams, Jessie; Brumby, Susan; Kennedy, Alison; Cotton, Jacquie
Abstract : Background: Unlike most workplaces, farms are both a workplace and a home often resulting in a blurred division between the two. Sadly, children represent 15% of all farm-related fatalities in Australia and this has remained consistent over the last 20 years. Additionally, child farm-related injury statistics have been interpreted without an understanding of the behaviours, attitudes and actions of children and their parents on farms. Methods: To develop two surveys that will assist in understanding the vulnerability of children in these environments a modified Delphi study was undertaken. The surveys will be completed by Victorian children (5–14 years) and their parent/s to explore children's exposure to farming hazards, risk-taking behaviours, attitudes towards safety measures and their experience of farm-related injury. Results: The use of the modified Delphi process allowed for effective co-design between farming, injury and industry professionals to develop two validated surveys. The parent and child survey results will describe activities children frequently participate in and explore the factors influencing parents' decision making in regard to their child's engagement on Victorian farms. Conclusion: As farming populations are heterogeneous these surveys can be used across varying farming populations and industries to understand child farm safety and the behaviours and attitudes of children and their parents. These results should inform the development of targeted and culturally appropriate injury prevention strategies. Learning outcomes: Understanding the common behaviours and attitudes of children and their parent/s on farms is vital in reducing the rate of fatal and non-fatal child farm injuries.